2000
DOI: 10.1021/jp001344e
|View full text |Cite
|
Sign up to set email alerts
|

The Zeno (Z = 1) Behavior of Equations of State:  An Interpretation across Scales from Macroscopic to Molecular

Abstract: The regularity exhibited by fluids along the contour of the unit compressibility factor in the temperaturedensity plane, where Z t PV/RT ) 1, is explored as a means for testing and improving the volumetric equations of state. For a wide range of pure fluids, this contour, known as the Zeno line, has been empirically observed to be nearly linear from the Boyle temperature of the low-density vapor to around the triple point in the liquid region. The Z ) 1 contour thus offers a quantitative criterion for interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 31 publications
2
77
0
Order By: Relevance
“…It has been found that along the contour defined by Z =1, where the compression factor is the same as for an ideal gas, the density of studied liquids is nearly linear function of temperature [47]. Along the entire Zeno contour, the attractive and repulsive contributions to the intermolecular potential are in dynamic balance.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that along the contour defined by Z =1, where the compression factor is the same as for an ideal gas, the density of studied liquids is nearly linear function of temperature [47]. Along the entire Zeno contour, the attractive and repulsive contributions to the intermolecular potential are in dynamic balance.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that along the contour defined by Z = 1, where the compressibility factor is the same as for an ideal gas, the density of studied liquids is nearly linear function of temperature [19]. Along the entire Zeno contour, the attractive and repulsive contributions to intermolecular potential are in dynamic balance.…”
Section: Resultsmentioning
confidence: 99%
“…Here and below, P is the system pressure, Т is the temperature in terms * Based on the Proceedings of the XIV Russian Conference on the Thermophysical Properties of Substances (RCTP- 14), Kazan, October 2014.…”
Section: The Van Der Waals Equation and The Virial Decompositionmentioning
confidence: 99%
“…However, the new scaling laws are not necessarily related to the WE, like, for example, the law of the rectilinear diameter of a binodal [3]. They may concern various characteristics of a substance at the critical point and along the phase transition lines [3][4][5][6][7][8][9] or can be related to the universal behavior of some geometric lines on the phase plane [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Some combinations are also possible [21].…”
Section: Introductionmentioning
confidence: 99%